Improvement Of Self Efficacy On Early Mobilization Capabilities In Post Sectio Caesaria - Kusumaningrum, Andri Tri; Kartikasari, Ratih Indah (Universitas Islam Lamongan, 2020)
Early mobilization of mothers after cesarean section (SC), is very important in the recovery of the mother's condition to immediately increase the independence of the mother. The independence of post SC mothers is needed so that mothers can adapt to their new roles. The initial survey results of post SC post partum mothers 24 hours, 6 mothers on day 1, 2 (33.3%) have not been able to mobilize early and 4 (66.6%) mothers can move their legs, tilted right and left. This shows that early mobilization is not yet in stages. The purpose of this study was to determine the effect of increasing self-efficacy with the ability to mobilize early.The quantitative research design uses quasi experimental design with posttest only design with control group. The population of all post SC postpartum mothers in the puerperium with a sample size of 34, used a simple random sampling method. The independent variable research increased self efficacy while the dependent variable was early mobilization ability. Data collection uses a checklist and observation sheet. The collected data were analyzed using Independent Test sample T Test, the results obtained p = 0,000 (P <0.05), showing Ho is rejected means that there is an influence of efforts to increase self efficacy on the ability of mothers to mobilize early.It can be concluded that self efficacy is one aspect that can improve the ability of early mobilization of post SC postpartum mothers according to stages so that it can help the recovery of maternal conditions during the postpartum period.